+0  
 
0
233
1
avatar

f(x)=7^x then f(x+3)-f(x+1) equals

Guest Nov 5, 2017

Best Answer 

 #1
avatar+7339 
+1

f(x)  =  7^x

 

f(x + 3)  =  7^(x + 3)     and     f(x + 1)  =  7^(x + 1)

 

So

 

f(x + 3) - f(x + 1)  =  7^(x + 3) - 7^(x + 1)

 

Remember that   xa * xb  =  xa+b  . So...

 

f(x + 3) - f(x + 1)  =  7^x  *  7^3  -  7^x  *  7^1

 

                            =  7^x  *  343  -  7^x  *  7             Factor out a  7^x  from both terms.

 

                            =  7^x  *  (343  -  7)

 

                            =  7^x  *  336

hectictar  Nov 5, 2017
 #1
avatar+7339 
+1
Best Answer

f(x)  =  7^x

 

f(x + 3)  =  7^(x + 3)     and     f(x + 1)  =  7^(x + 1)

 

So

 

f(x + 3) - f(x + 1)  =  7^(x + 3) - 7^(x + 1)

 

Remember that   xa * xb  =  xa+b  . So...

 

f(x + 3) - f(x + 1)  =  7^x  *  7^3  -  7^x  *  7^1

 

                            =  7^x  *  343  -  7^x  *  7             Factor out a  7^x  from both terms.

 

                            =  7^x  *  (343  -  7)

 

                            =  7^x  *  336

hectictar  Nov 5, 2017

28 Online Users

avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.